الوصل في سورة فُصِّلت دراسة بلاغيّة نصيّة - جمانة دايخة; حياة عامر (University of Eloued جامعة الوادي, 2025)
الملخص: تسعى هذه الدراسة المعنونة ب:"الوصل في سورة فُصلت دراسة بلاغية نصية" إلى تسليط الضوء على ظاهرة الوصل في سورة فصلت؛ من منطلق عدها نقطة التقاء بين علمي لسانيات النص والبلاغة؛ فقد برز في لسانيات النص اهتمام خاص بالوصل؛ حيث أدرج من بين أهم أدوات الاتساق التي تساهم في التماسك الشكلي للنصوص، لكن اتضح من خلال هذه الدراسة أن الوصل له دور حتى في الانسجام بين الجمل، وذلك من خلال العلاقات الدلاية التي ظهرت من خلال الاتفاق بين الموضع والنوع، وفي البلاغة العربية دُرس الوصل في ثنائية " الفصل والوصل" التي عُدت من حدود البلاغة وقيل أن البلاغة تتطلب معرفة "الفصل والوصل" وخلصت هذه الدراسة إلى مجموعة من النتائج لعل منها: أن الوصل النصي أعم من الوصل البلاغي؛ حيث إن الوصل النصي يتجاوز مفهوم التعاطف بين الجمل إلى غيره من أنماط الربط، فيما تحصر بلاغة الوصل في التعاطف بالواو التي كان لها حضور كبير في سورة فصلت التي أفادت الجمع، وهذا الأخير أسهم في بيان الاستمرارية الدلالية في هذه السورة من منطلق الجمع بين المجمل وتفاصيله. Résumé : فرنسية أو انجلزية This study, entitled “Conjunction in Surat Fussilat: A Textual Rhetorical Study,” seeks to shed light on the phenomenon of conjunction in Surat Fussilat, based on its being a meeting point between the sciences of text linguistics and rhetoric. In text linguistics, special attention has been paid to conjunction, as it has been included among the most important tools of coherence that contribute to the formal coherence of texts. But it became clear through this study that the connection has a role even in the harmony between sentences, and that is through the semantic relationships that appeared through the agreement between the position and the type, and in Arabic rhetoric, the connection was studied in the duality of “separation and connection” which was considered among the limits of rhetoric and it was said that rhetoric requires knowledge of “separation and connection.” This study concluded with a set of results, perhaps including: that the textual connection is more general than the rhetorical connection, as the textual connection goes beyond the concept of sympathy between sentences to other types of connection, while the rhetoric of connection is limited to sympathy with the waw, which had a large presence in Surat Fussilat, which indicated the collection. The latter contributed to demonstrating the semantic continuity in this surah, based on combining the general and its details.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: لسانيات النص، البلاغة، الوصل، الاتساق، الانسجام; Textual linguistics. Rhetoric. Connection. Coherence. harmony.